PRESEPSI GURU TENTANG KINERJA ADMINISTRASI SEKOLAH DI MTsN 2 SOLOK - Lathifah, Najmi Diyana; Sabri, Ahmad; Hasnawati, Hasnawati (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2023)
Najmi Diyana Lathifah, with thesis title: "Teachers' Perceptions About the Competency of Administrative Staff at MTsN 2 Solok". In the Islamic education management department, Tarbiyah and Teacher Training Faculty, Imam Bonjol State Islamic University, Padang. This research is motivated by the problem of school administration staff not respecting other people's opinions, giving rise to unfavorable assumptions related to employee performance, there are still many files that have piled up and are not neatly arranged, the educational qualifications and technical competence of school administration staff are still not in accordance with Permendiknas Number 24 of 2008, and there is no information regarding teacher perceptions regarding the performance of school administration at MTsN 2 Solok. The aim of this research is to measure the personality competence, social competence, technical competence of MTsN 2 Solok educational staff. To measure teachers' perceptions of the performance of administrative staff at MTsN 2 Solok. The method used in this research is a quantitative method with a descriptive approach in the form of survey research. The population in this study were all MTsN 2 Solok teachers, totaling 66 teachers. With a questionnaire instrument that has 70 questions. Reliability test uses Cronbach's Alpha formula. The results of the research show that the teacher's perception of the performance of school administration staff at MTsN 2 Solok, personality competency is in the quite good category at 53.03% (35 teachers). Teachers' perceptions regarding the performance of school administration staff at MTsN 2 Solok based on social competence are in the good category as many as 48 teachers or 72.73%. Teachers' perceptions regarding the performance of MTsN 2 Solok school administration staff based on technical competency are in the good category as many as 31 teachers or 46.96%.